Implementation of Course-Mini Project (CMP) in Core Laboratory Course for the Attainment of Program Outcomes in Outcome Based Education - Bharath Pulavarthi, V. R. S. V.; Metri, Rajanikant A.; Dontham, Rajesh; Srikanth, I.; Bhattar, C. L. (Journal of Engineering Education Transformations, 2017)
In engineering education programs, students are expected to gain certain skill sets to address the global problems.Assessment of these skill sets by the instructor is one of the challenging task. This paper discusses the designed rubrics and the assessment tools used in order to attain graduate attributes to its best. The ’Automation and Control Laboratory’ course of Final Year B. Tech Electrical under-graduate programme is selected for the attainment of Program Outcomes. The assessment of the course is done through Continuous Assessment (CA) and Course-Mini Projects (CMPs). Implementation of different methodologies to assess the student’s skills are discussed in the paper. The correlation between assessment methods and CLOs and then POs is done. The attainment of POs is calculated after calculating Course Outcomes (COs) through direct and indirect methods.